Symbionts protect aphids from parasitic wasps by attenuating herbivore-induced plant volatiles - Frago, E; Mala, M; Weldegergis, B; Yang, C; McLean, A; Godfray, H; Gols, R; Dicke, M (Nature Publishing Group, 2017)
Plants respond to insect attack by releasing blends of volatile chemicals that attract their herbivores’ specific natural enemies, while insect herbivores may carry endosymbiotic microorganisms that directly improve herbivore survival after natural enemy attack. Here we demonstrate that the two phenomena can be linked. Plants fed upon by pea aphids release volatiles that attract parasitic wasps, and the pea aphid can carry facultative endosymbiotic bacteria that prevent the development of the parasitic wasp larva and thus markedly improve aphid survival after wasp attack. We show that these endosymbionts also attenuate the systemic release of volatiles by plants after aphid attack, reducing parasitic wasp recruitment and increasing aphid fitness. Our results reveal a novel mechanism through which symbionts can benefit their hosts and emphasise the importance of considering the microbiome in understanding insect ecological interactions.